INDUSTRIAL TESTS OF CURRENT DISTRIBUTION DYNAMICS IN THE BRUSH-CONTACT APPARATUS OF THE TURBO-GENERATOR (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The article is devoted to analysis of the results of industrial tests of current distribution dynamics in the brush-contact apparatus of the turbo-generator TVV-800 (800 MW) using a microprocessor based monitoring system. New methods of assessing the quality of current-collecting devices functioning is developed, allowing to assess current transfer in dynamics and to determine their quality characteristics. New trends of current distribution dynamics between the parallel brushes that allow on the basis of statistical and variance analysis to develop practical recommendations for maintenance of these devices are revealed. The results of the research in the form of scientific articles are published for the first time.